An Overview of Immunotherapeutic Approaches Against Canine Visceral Leishmaniasis: What Has Been Tested on Dogs and a New Perspective on Improving Treatment Efficacy - Gonçalves, Ana Alice Maia; Leite, Jaqueline Costa; Resende, Lucilene Aparecida; Mariano, Reysla Maria da Silveira; Silveira, Patricia; Melo-Júnior, Otoni Alves de Oliveira; Ribeiro, Helen Silva; de Oliveira, Diana Souza; Soares, Diogo Fonseca; Santos, Thaiza Aline Pereira; Marques, Alexandre Ferreira; Galdino, Alexsandro Sobreira; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Visceral leishmaniasis (VL), caused by digenetic protozoa of the genus Leishmania, is the most severe form of leishmaniasis. Among the species responsible for VL, Leishmania infantum is considered a zoonosis whose main reservoir is the dog. Canine visceral leishmaniasis (CVL) can lead to the death of the animal if left untreated. Furthermore, the available pharmocologial treatment for CVL presents numerous disadvantages, such as relapses, toxicity, drug resistance, and the fact treated animals continue to be reservoirs when treatment fails to achieve parasitological cure. Moreover, the available VL control methods have not been adequate when it comes to controlling parasite transmission. Advances in immune response knowledge in recent years have led to a better understanding of VL pathogenesis, allowing new treatments to be developed based on immune system activation, often referred to as immunotherapy. In fact, well defined protocols have been described, ranging from the use of immunomodulators to the use of vaccines. This treatment, which can also be associated with chemotherapy, has been shown to be effective in restoring or inducing an adequate immune response to reduce parasitic burden, leading to clinical improvement. This review focuses on immunotherapy directed at dogs infected by L. infantum, including a literature review of what has already been done in dogs. We also introduce a promising strategy to improve the efficacy of immunotherapy.